Insect Biodiversity in Brinjal Agro-Ecosystem (Biological Sciences - PJSIR, 2019)
The experiment on insect biodiversity in brinjal (Solanum melongena L.) agro-ecosystem was conducted at village Mushtaque Kaleri near Tandojam, Hyderabad, Sindh, Pakistan during winter season 2015-2016. For this purpose ½ acre of brinjal crop was cultivated. Collection was done once a week through sweep net method. Data was collected by examining 30 plants and analyzed by using Shannon diversity index. The results showed that in brinjal agro-ecosystem 27 species of insects were recorded from 10th of December 2015 to 5th of March 2016. Among them 19 species were pests and 8 species were predators and pollinators. The highest diversity (H' =3.33) was recorded on 23 February, 2016 while the minimum (H' =2.15) was recorded on 01 December, 2015. The highest diversity (Hmax) 3.29 was recorded on 29 December, 2015 and 16 February, 2016 however, the lowest diversity (Hmax) 3.09 was recorded on 01 December, 2015 and 08 December, 2015. The maximum evenness (J' =1.02) was recorded on 26 January, 2016 and 23 February, 2016, respectively. Whereas minimum evenness (J' =0.69) was recorded on 01 December, 2015. The maximum richness (D=0.27) was recorded in two observations on 29 December, 2015 and 16 February, 2016. However, minimum richness (D=0.22) was recorded on 01 December, 2015 and 08 December, 2015 in brinjal agro-ecosystem.